MODIFICATION OF THE COCONUT GRAINING MACHINE HOPPER INTO A RED GINGER GRAINING MACHINE - Abdul Hakim; Karyanik Karyanik; Muanah Muanah (Universitas Muhammadiyah Mataram, 2025)
@font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536869121 1107305727 33554432 0 415 0;p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-AU; mso-fareast-language:ZH-CN;.MsoChpDefault mso-style-type:export-only; mso-default-props:yes; mso-ansi-language:EN-AU; mso-fareast-language:EN-ID;div.WordSection1 page:WordSection1;The manual red ginger grating process in home industries and micro, small, and medium enterprises faces various challenges, such as being time-consuming, requiring a large amount of labor, and producing less than optimal extraction. Commercially available ginger grating machines are often not effective and efficient enough, resulting in low production capacity and suboptimal quality. Therefore, technological innovation is needed in the form of modifying a coconut grater machine into a red ginger grater machine to increase productivity, effectiveness, efficiency, and quality of grated red ginger. This study aims to carry out these modifications, as well as to determine the working mechanism of the machine before and after modification, and to assess the machine's performance under these two conditions. The research method used is experimental with the design and modification of a coconut grater into a red ginger grater, then performance testing is carried out at the Workshop Laboratory of the Faculty of Agriculture, Muhammadiyah University of Mataram. The variables tested include machine working capacity, efficiency, volume of ginger juice, pulp weight, and water content. Data were analyzed using the ANOVA method and continued with the Honestly Significant Difference (HSD) test if there is a significant difference. The analysis results show that statistically there is no significant difference between the machines before (P1) and after (P2) modification on the tested parameters, because the F-count value is smaller than the F-table. However, descriptively, the P1 machine has a slightly higher working capacity (242.83) than P2 (241.48), with a difference of 1.35, and the machine efficiency shows good performance for both conditions. This research is the basis for the development of a more efficient and high-quality red ginger grater in the future.